Konsep Diri Positif Melalui Pemaknaan Hijrah Generasi Milenial Dilihat dari Persfektf Pendekatan Konseling Humanistik - Hartika Utami Fitri; Kushendar Kushendar (Kuras Institute, 2021)
The meaning of hijrah is also a trend to show off that it has routine activities that are useful not on the basis of the heart's movement to change, then the meaning of hijrah is also limited to changing clothes that are more closed and more arrogant, of course this has the wrong meaning. Full meaning of something will certainly produce good conclusions, especially on the meaning of hijrah. Having the wrong meaning of hijrah that is not in accordance with Islamic values ​​will certainly make a teenager who does not have a positive self-concept. The research method used was experimental, pretest-posttest control group design, with the mediator variable that will be involved in this study. Involving 14 research subjects who were selected purposively from 114 first year students of BPI UIN Raden Fatah Palembang. The research instrument used was a self-concept scale consisting of 16 items. The results of the analysis using the Regression Test to show that there is a significant relationship and increase between positive self-concept and the meaning of hijrah using a humanistic counseling. The findings of this study also show that the experimental group using a humanistic approach experienced a significant increase in self-concept through the meaning of hijrah. There is a significant relationship between the meaning of hijrah and self-concept.